THE EFFECT OF SERVICE QUALITY DIMENSIONS ON HEMODIALYSIS PATIENT SATISFACTION IN INDONESIA - Hartanti, Lia Kurnia; Antonio, Ferdi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2022)
Background: Chronic kidney disease is a catastrophic disease ranked second in Indonesia for high health costs. The number of renal units in Indonesia has rapidly increased since the launch of the National Health Insurance program in 2014. Its increase was accompanied by the increased number of patients. Aim: This study analyzed the effect of service quality dimensions on patient satisfaction with hemodialysis care. Methods: This study used a cross-sectional design and a quantitative method. It retrieved data from respondents who had undergone hemodialysis care at hospitals and clinics in Jakarta and surroundings. The PLS-SEM approach was used to analyze the data. Results: Eight service dimensions were proven to influence the overall service quality and directly impact patient satisfaction. The influential dimensions included facilities and organization of the service, care by attending nurses and assistants, attention to psychological and administrative issues, medical attention and care, nutrition attention and care, medication supply and quality, features and administration process, attention and care given by the head nurse. All of these dimensions affected patient satisfaction as a dependent variable. This study has strong predictive accuracy, and thus it can be replicable in future research with different populations. Conclusion: This study demonstrated eight service quality dimensions that affect service quality and directly impact satisfaction of hemodialysis patients both with hospital and clinic services.